The Growing Evidence for Demonic Possession: What Should Psychiatry's Response be? - Betty, Stafford (Journal of religion and health, 2005)
Evidence of evil spirits is voluminous and comes from many cultures, both ancient and modern. Cases from China, India, and the United States are examined and evaluated. The actual experience of spirit victims, the universality of spirit oppression, the superhuman phenomena associated with "possession," and the comparative success of deliverance and exorcism vs. psychiatry are considered. Potential arguments against the spirit hypothesis center on the antecedent improbability of spirits, multiple personality disorder, and the effectiveness of medication; but these can be countered. Psychiatrists should question their materialist assumption that mental illness is strictly a matter of an aberrant brain, carefully examine the literature of possession, experiment to determine why exorcists and deliverance ministers often succeed where psychiatry fails, and develop a more complete inventory of techniques for healing the complete person.